Mechanism of Deoxygenation and Cracking of Fatty Acids by Gas-Phase Cationic Complexes of Ni, Pd, and Pt - Kevin Parker; Victoria Pho; Richard A. J. O’Hair; Victor Ryzhov (Reactions, 2021)
Deoxygenation and subsequent cracking of fatty acids are key steps in production of biodiesel fuels from renewable plant sources. Despite the fact that multiple catalysts, including those containing group 10 metals (Ni, Pd, and Pt), are employed for these purposes, little is known about the mechanisms by which they operate. In this work, we utilized tandem mass spectrometry experiments (MSn) to show that multiple types of fatty acids (saturated, mono-, and poly-unsaturated) can be catalytically deoxygenated and converted to smaller hydrocarbons using the ternary metal complexes [(phen)M(O2CR)]+], where phen = 1,10-phenanthroline and M = Ni, Pd, and Pt. The mechanistic description of deoxygenation/cracking processes builds on our recent works describing simple model systems for deoxygenation and cracking, where the latter comes from the ability of group 10 metal ions to undergo chain-walking with very low activation barriers. This article extends our previous work to a number of fatty acids commonly found in renewable plant sources. We found that in many unsaturated acids cracking can occur prior to deoxygenation and show that mechanisms involving group 10 metals differ from long-known charge-remote fragmentation reactions.